Designing learning with digital technologies - (:unkn) unknown (Routledge, 2025)
This book offers a multimodal perspective on how to design meaningful learning experiences with digital technologies. Digital education is of increasing importance in today’s digital society and the editors bring together international thought-leaders and well-established academics across geographical regions to explore the topic. The book addresses the need to design learning with digital technologies, especially in a post-pandemic environment where blended learning has become ubiquitous. The book is organised around five themes: designing learning, digital learning designs, digital learning with embodied teaching, digital learning interactions, and digital multimodal literacies. The chapters focus on digital technologies as multimodal semiotic resources and the educational implication of each theme is drawn out from illustrative cases across contexts of learning. Essential reading for researchers and postgraduate students, this book offers state-of-the-art thinking on how educators can design new learning experiences for students through the meaningful and effective use of digital technologies.
Keywords: digital technologies; designing learning; multimodality